The Effect of English Songs on Pronunciation Skills of Vocational High School Students - Leni Yuniati; Ahmad Syafiq; Dyah Sih Pratiwi (STKIP PGRI Lubuklinggau, 2025)
Abstract One of the goals of this research is to find out whether pupils' pronunciation improves after listening to English songs taught at a vocational school in Bandar Lampung. Two cycles of three sessions each were used to conduct the study using a Classroom Action Research (CAR) design. In the 2023–2024 school year, thirty tenth graders served as the subjects. Assessments of pronunciation, classroom observations, and reflective notes were utilized to gather data. As a consequence of using Ed Sheeran's